PO.6.131 A randomized, double-blind, placebo controlled study of the safety, tolerability, pharmacokinetics, and pharmacodynamics of ALPN-303, a potent dual baff/april inhibitor, in adult healthy volunteers. (27th September 2022) - Harrison, P; Lickliter, J; Dillon, S; Manjarrez, K; Smith, A; Lessig, M; Sanderson, R; Chunyk, A; Zayed, H; Peng, S
Abstract : Background: Therapeutic agents targeting the B-cell cytokines B-cell activating factor of the TNF family (BAFF) and/or a proliferation-inducing ligand (APRIL), including the monoclonal antibody belimumab and the wild-type (WT) TACI-Fc fusion proteins atacicept and telitacicept, have demonstrated promising clinical potential in rheumatic diseases like systemic lupus erythematosus (SLE) and/or other B-cell-related diseases such as autoantibody-related nephritides. ALPN-303 is an Fc fusion protein of a variant, engineered TACI domain which mediates significantly more potent inhibitory activity than WT TACI-Fc or BAFF- or APRIL-specific monoclonal antibodies, with enhanced pharmacokinetic (PK) and immunomodulatory properties versus WT TACI-Fc in preclinical studies. 1, 2 ALPN-303 may therefore significantly improve clinical outcomes in SLE and other B-cell-related diseases. Purpose: To evaluate the safety, tolerability, PK, and pharmacodynamics (PD) of ALPN-303 in adult healthy volunteers (HV). Methods: In this first-in-human study (NCT05034484 ), adult HVs are enrolled in single ascending dose cohorts of intravenously (IV) or subcutaneously (SC) administered ALPN-303. For each IV cohort, the first 2 subjects are randomized 1:1 to receive ALPN-303 or placebo, followed by the remaining 4 subjects randomized 3:1 to receive ALPN-303 or placebo. For each SC cohort, HVs are randomized 4:2 to receive a single SC dose of ALPN-303 or placebo. All subjects are followed to assess safety and PK of ALPN-303, to measure levels of circulating immunoglobulins (Ig), and to characterize leukocyte populations in peripheral blood by flow cytometry. Results: ALPN-303 has been well tolerated in all IV and SC cohorts evaluated to date, and overall exhibits dose-related PK and expected PD effects on circulating Ig levels, including reductions in serum Ig ( Figure 1 ). To date there have been no treatment-related serious adverse events, no infusion-related reactions, and no adverse trends in safety laboratory parameters reported in any of the dosed cohorts. The remainder of dose escalation is expected to be completed by the time of the meeting; the presentation will include all available safety, PK, and PD (circulating Ig and B-cell population) data. Conclusion: In this first-in-human study, ALPN-303 to date demonstrates acceptable preliminary safety and tolerability, and exhibits expected PD effects on circulating Ig. These findings support future clinical development of ALPN-303 in patients with SLE and/or other B-cell- and/or autoantibody-related diseases. References: Dillon SR, Evans LS, Lewis KE, et al . OP0039 ALPN-303, an enhanced, potent dual BAFF/APRIL antagonist engineered by directed evolution for the treatment of systemic lupus erythematosus (SLE) and other B cell related autoimmune diseases. Annals of the Rheumatic Diseases 2021;80 :21. Dillon SR, Evans LS, Lewis KE, et al . ALPN-303, an enhanced, potent dual BAFF/APRIL antagonist engineered by directed evolution for the treatment of systemic lupus erythematosus (SLE) and other B cell-related diseases. Arthritis Rheumatol 2021;73 (suppl 10).